190k views
4 votes
Solve the equation 8-6z=26

User Ildjarn
by
4.2k points

2 Answers

6 votes

8-6z=26

8-8-6z=26-8

-6z=18

divide by -6 for -6z and 18

-6z/-6=18/-6

z=-3

Check answer by using substitution method

8-6(-3)=26

8+18= 26

26=26

Answer is z=-3

User ZacWolf
by
4.6k points
2 votes

Answer:

answer - 3

Explanation:

8 - 6z = 26 Subtract 8 from both sides.

8-8 - 6z = 26 - 8

- 6z = 18 Divide by - 6

-6z/-6 = 18/-6 Do the division. Note: you must leave the letter with 1 in front of it.

z = - 3

User Ahelwer
by
5.1k points